1. Consider the following statements. $$(w \vee x \vee y)\land(\left(w \wedge y\right) \vee \neg z)\land(\neg z \wedge \left(y \vee \neg w\right))\land(\left(w \wedge z\right) \vee \neg y)$$ Mark each of the following assignments under which the statement is True.
    w=F, x=F, y=F, z=T
    w=T, x=F, y=T, z=F
    w=T, x=T, y=T, z=T
    w=F, x=T, y=F, z=F

  2. Consider the following statements. $$(y \wedge \left(z \vee \neg x\right))\land(\neg w \wedge \left(z \vee \neg y\right))\land(w \vee y \vee z)\land(z \vee \left(w \wedge \neg y\right))\land(\left(w \wedge \neg y\right) \vee \neg x)$$ Mark each of the following assignments under which the statement is True.
    w=T, x=T, y=T, z=F
    w=F, x=F, y=T, z=T
    w=F, x=T, y=F, z=T
    w=T, x=F, y=T, z=F

  3. Consider the following statements. $$(\left(z \wedge \neg w\right) \vee \neg y)\land(\neg x \wedge \left(w \vee \neg y\right))\land(w \vee \left(y \wedge z\right))\land(x \vee y \vee z)\land(\left(w \wedge x\right) \vee \neg y)\land(\left(y \wedge \neg z\right) \vee \neg x)$$ Mark each of the following assignments under which the statement is True.
    w=T, x=T, y=F, z=F
    w=T, x=F, y=T, z=T
    w=T, x=F, y=F, z=T
    w=T, x=F, y=F, z=F

  4. Consider the following statements. $$(\left(y \wedge \neg z\right) \vee \neg x)\land(w \wedge \left(y \vee z\right))\land(z \vee \left(\neg x \wedge \neg y\right))\land(y \wedge \left(z \vee \neg w\right))$$ Mark each of the following assignments under which the statement is True.
    w=F, x=F, y=T, z=T
    w=F, x=F, y=F, z=F
    w=F, x=T, y=T, z=F
    w=T, x=F, y=T, z=T

  5. Consider the following statements. $$(w \vee \left(x \wedge \neg y\right))\land(\left(y \wedge \neg w\right) \vee \neg z)\land(\left(y \wedge \neg z\right) \vee \neg w)\land(\left(z \wedge \neg y\right) \vee \neg w)$$ Mark each of the following assignments under which the statement is True.
    w=F, x=T, y=F, z=F
    w=F, x=F, y=T, z=T
    w=F, x=F, y=T, z=F
    w=T, x=T, y=F, z=T

  6. Consider the following statements. $$(\left(y \wedge \neg w\right) \vee \neg x)\land(y \wedge \left(x \vee z\right))\land(w \wedge \left(y \vee z\right))\land(\left(w \wedge \neg y\right) \vee \neg x)$$ Mark each of the following assignments under which the statement is True.
    w=F, x=T, y=T, z=T
    w=T, x=F, y=T, z=F
    w=F, x=F, y=T, z=T
    w=T, x=F, y=T, z=T